Twitter as a Tool of Propaganda: A Discourse Analysis of Pakistan Tehreek-e-Insaf (PTI) Twitter Propaganda on the Non-Confidence Movement - Lashari, Sarmad Aftab; Bhand, Ahsanullah; Katohar, Sajjad Gul (Annals of Human and Social Sciences, 2024)
This study investigates PTI’s use of Twitter as a tool for propaganda in political crises and highlights the potency of Twitter in shaping the political landscape in Pakistan. The use of social media as a tool for political affairs has long been applied throughout the world by different world leaders and political parties. Similarly, Pakistan is no exception. Pakistan Tehreek-e-Insaf’s (PTI) use of Twitter as a propaganda tool during the non-confidence movement to influence public opinion and mobilize support is used as the case study. This research venture is based on the qualitative analysis of secondary sources. The information about the propaganda of PTI is sought from Twitter. The Tweets of Imran Khan have been investigated to address the core concerns of this study. Findings show that PTI’s Twitter campaign employed a blend of emotional appeals, nationalistic rhetoric, and discrediting political opponents to shape narratives and control discourses. Hashtags, multimedia content, and coordinated tweet storms were instrumental in strengthening PTI’s message. Thus, Twitter served as a critical platform for PTI to sustain its political narrative and counter opposition efforts. Therefore, this study recommends the formation of proper legislation for the proper use of social media to address such dangerous emerging trends in the country.